Investigating the Impact of Institutions on Small Business Creation Among Saudi Entrepreneurs - Alshebami, Ali Saleh; Seraj, Abdullah Hamoud Ali (Frontiers in Psychology, 2022)
Institutions significantly impact people’s attitudes and behaviors, both favorably and negatively. The purpose of this article is to examine the influence of several institutions on the intentions and decisions of Saudi entrepreneurs to start a business. Accordingly, the study on which this article is based used cross-sectional data of 3,376 respondents obtained from the Global Entrepreneurship Monitor (GEM) in 2016. The findings demonstrated that insufficient business legislations and policies have a detrimental impact on the ability to start small businesses. Furthermore, it was discovered that the more media attention is given to successful entrepreneurs, the greater the likelihood of small businesses being established. Surprisingly, the typically high regard for successful entrepreneurs had no positive impact on the establishment of small businesses in Saudi Arabia. Moreover, there was no negative impact of fear of failure on the likelihood of starting small firms. Finally, the influence of control variables, such as age and gender, was also varied. Because the study was limited to the context of Saudi Arabia, future research could focus on expanding the analysis to other Gulf countries and including more institutions.